PERANCANGAN DAN PEMBUATAN SISTEM INFORMASI AKUNTANSI PADA TOKO SUNTECH - Sutikdja, Wijaya Nugrogho; -, Yulia; Dewi, Lily Puspa (Jurnal Infra, 2014)
ABSTRACT : SunTech Shop is a company engaged in the sale and purchase of electric industrial raw materials that their daily activities are covering the purchase and sale of merchandise. During that time, SunTech Stores still use the manual method to produce financial statements and journal needed. All transactions are recorded at the end of working hours each day so it cannot provide information in a timely and accurate manner. Therefore, in this thesis are designed and manufactured an accounting information system that helps the problem to obtain the required information quickly, accurately and is also expected to avoid or minimize the occurrence of errors arising from the recording of the companys activities, and generate reports useful for progress.System designâs scheme use Data Flow Diagram and Entity Relationship Diagram. Database made by using Microsoft SQL Server 2005. Application made with Programming Language Microsoft Visual Studio 2005 . NET. Program which has been made cover database master for goods, supplier, purchase and sale transaction, and also accounting process relate to making of journal automatically and adjustment journal manually and also financial statement automatically.Â From the results of the testing program indicate that the program is capable of processing accounting data relating to the purchase and sale of automatic and produce information in the form of managerial reports (report purchases, sales and debt), Â journals (general journal, purchases journal, cash disbursements journal, cash receipts journal and general ledger) and financial statements (income statement, changes in equity and balance sheet) are accurate (according with the manual).